ISOLASI DAN KARAKTERISASI ZAT WARNA Capsicum frutescens - Bimo Budi Santoso (FMIPA Universitas Papua, 2002)
Isolation and characterization of pigments from C. frutescens have been done. Three components (pigments) were eluted using column chromatography namely yellow pigment, orange pigment, and red pigment. Solvents used to separate the pigments were hexane/dichloroethane, dichloroethane, dichloroethane/methanol and chloroform/dichloroethane. Isolated pigments were subjected to TLC to prove the purity and to get the Rf value of the isolates. Then, the pure isolates were subjected to UV spectroscopy to get UV spectrum. Base on the data of polarity, pigment color, Rf value, and UV spectrum, the isolated components of C. frutescens are probably b-carotene (yellow pigment), phenolic or flavonoid compound (orange pigment), and capsanthin (red pigment).